of Students' Mathematical Comprehension Ability on Two Variable Linear Equation System (SPLDV) Materials in Class X Students of SMAN 1 MONTASIK - Julia Julia; Nazariah Nazariah; Nailul Autahry (Prodi Tadris Matematika Universitas Muhammadiyah Aceh, 2021)
Understanding is a translation of the term understanding which is defined as the absorptionof the meaning of a material being studied. This can also be seen in the results of the 2015PISA (Program for International Student Assessment) test, that the mathematical ability ofIndonesian students is at a low level, even 42.3% of students have not yet reached level 1 of6 proficiency levels for mathematics and science and make Indonesia a nation. is in position69 of the 76 participating countries. This research is an exploratory qualitative research thataims to determine students' mathematical understanding ability in solving math problemsbased on students' mathematical abilities. The research method used is descriptive. Thesubjects in this study were 6 students and class X students who had different mathematicalabilities, namely 2 students with high abilities, 2 people with moderate abilities, 2 peoplewith low abilities who were taken at Senior High School 1 MONTASIK school. Thisresearch was conducted to determine the tendency of mathematical understanding abilityaccording to students' ability to solve story problems about a system of linear equations oftwo variables. The results of data analysis show that (1) Students who have a high ability tounderstand mathematical abilities have been able to solve problems properly and correctly,although there are still some who cannot. 2) Students who have moderate ability tomathematical understanding abilities are able to make examples, make what is known andwhat is asked, have not been able to run or operate story problems and are able to makeconclusions. (3) Students who have low ability to understand mathematical abilities havebeen able to make examples, but have not made what is known and asked, run or operatestory problems and make conclusions.